2012
DOI: 10.21608/eajbsa.2012.14821
|View full text |Cite
|
Sign up to set email alerts
|

The potency of Chloropyrifos and Camphor extract on Spodoptera littoralis (BOISD.)

Abstract: The biological and biochemical effects chloropyrifos, camphor extract and their combination were studied against the 4 th instars of Spodoptera littoralis under semi-field conditions. The results indicated that the LC 50 for chloropyrifos was 0.08 ppm and 13.3 x 10 3 ppm for the camphor extract. The estimated Co-toxicity factor was 13.2 So, there is an additive effect between camphor oil and chloropyrifos against S. littoralis.Oil extract of camphor prolonged larval and pupal duration also the same effect happ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
2
3
0
Order By: Relevance
“…They also found that camphor oil did not affect the number of total lipids in S. littoralis larvae in contrast with the present study that showed a significant reduction in the number of total lipids. In the present study, the camphor oil caused a significant reduction in the total protein content; this was in agreement with Osman et al, (2012) who found that total protein content decreased in the 4 th larval instar of S.littoralis when treated with camphor oil. The same result was obtained by Fetoh et al, (2013) who investigated total protein in S. littoralis larvae which was significantly decreased after treatment with camphor extract.…”
Section: Biochemical Changes Induced By Camphor Oilsupporting
confidence: 93%
“…They also found that camphor oil did not affect the number of total lipids in S. littoralis larvae in contrast with the present study that showed a significant reduction in the number of total lipids. In the present study, the camphor oil caused a significant reduction in the total protein content; this was in agreement with Osman et al, (2012) who found that total protein content decreased in the 4 th larval instar of S.littoralis when treated with camphor oil. The same result was obtained by Fetoh et al, (2013) who investigated total protein in S. littoralis larvae which was significantly decreased after treatment with camphor extract.…”
Section: Biochemical Changes Induced By Camphor Oilsupporting
confidence: 93%
“…In addition, exposure of chlorosan (chloropyrifos 24% + cypermethrin 5%), engeo (thiamethoxam 14.1% + lambda-cyclithrin 10.6%), cygron (flufenoxuron 3% + alpha-cypermethrin7%) and feroban (chloropyrifos 47.5% + lufenuron 2.5%) caused significant reduction in total protein level in the larva of S. littoralis 26 . Our present findings are in accordance with the above results as reported in case of S. littoralis 26,28,50 . It appears that reduction in protein level in haemolymph and fat body, in the present study, may be due to the insecticidal ( chlorpyrifos-methyl+ methoprin ) inhibition of amino acid incorporation into protein, as reported in case of Triatoma infestans 1 in relation to higher DDT concentration.…”
Section: Fat Bodysupporting
confidence: 94%
“…On the contrary, lower DDT concentrations increased the protein content of Triatoma infestans by enhancing the amino acid incorporation into protein while higher DDT concentrations inhibited the amino acid incorporation into protein causing adverse effect on protein biosynthesis 1 . Application of a mixture of chlorpyrifos and camphor extract significantly decreased the total protein level by 13.5% in the larva of cotton leafworm, Spodoptera littoralis while this level was reduced to 31 and 26% following the exposure of camphor extract and chlorpyrifos repectively 50,28 . In addition, exposure of chlorosan (chloropyrifos 24% + cypermethrin 5%), engeo (thiamethoxam 14.1% + lambda-cyclithrin 10.6%), cygron (flufenoxuron 3% + alpha-cypermethrin7%) and feroban (chloropyrifos 47.5% + lufenuron 2.5%) caused significant reduction in total protein level in the larva of S. littoralis 26 .…”
Section: Fat Bodymentioning
confidence: 97%
See 1 more Smart Citation
“…This bioactivation is done by esterase enzymes (Alves et al 2008). Chlorpyrifos was found to increase the activity of esterases in S. littoralis (Osman et al 2012). This increased activity might increase the bioactivation rate of indoxacarb which might be the explanation of the strong potentiation effect shown in the I/Ch mixture (Table 3, Fig.…”
Section: Discussionmentioning
confidence: 91%